Synergistic Effects of Plant Growth Promoting Rhizobacteria and Chitosan on In Vitro Seeds Germination, Greenhouse Growth, and Nutrient Uptake of Maize (Zea mays L.). (20th January 2016) - Agbodjato, Nadège A.; Noumavo, Pacôme A.; Adjanohoun, Adolphe; Agbessi, Léonce; Baba-Moussa, Lamine
Abstract : This study aimed to assess the effects of three plant growth promoting rhizobacteria (PGPR) and chitosan either singly or in combination on maize seeds germination and growth and nutrient uptake. Maize seeds were treated with chitosan and bacterial solution. The germination and growth tests were carried out in square Petri dishes and plastic pots. The combination chitosan- A. lipoferum - P. fluorescens has increased the seeds vigor index up to 36.44% compared to the control. In comparison to the control, P. putida has significantly improved root weight (44.84%) and germinated seed weight (31.39%) whereas chitosan- P. putida has increased the shoot weight (65.67%). For the growth test, the maximal heights (17.66%) were obtained by plants treated with the combination A. lipoferum-P. fluorescens-P. putida . Chitosan- P. fluorescens induced the highest increases of leaves per plant (50.09%), aerial (84.66%), and underground biomass (108.77%) production. The plants inoculated with A. lipoferum had the large leaf areas with an increase of 54.08%, while combinations P. fluorescens-P. putida and chitosan -A. lipoferum improved the aerial and underground dry matter of plants to 26.35% and 18.18%. The nitrogen content of the plants was increased by chitosan -A. lipoferum-P. fluorescens-P. putida with an increasing of 41.61%. The combination of chitosan and PGPR can be used as biological fertilizers to increase maize production.